2020
DOI: 10.18632/aging.103846
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing endoplasmic reticulum stress-related autophagy attenuates retinal light injury

Abstract: Excessive light exposure is a principal environmental factor, which can cause damage to photoreceptors and retinal pigment epithelium (RPE) cells and may accelerate the progression of age-related macular degeneration (AMD). In this study, oxidative stress, endoplasmic reticulum (ER) stress and autophagy caused by light exposure were evaluated in vitro and in vivo . Light exposure caused severe photo-oxidative stress and ER stress in photoreceptors (661W cells) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 54 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…Following PERK downregulation, ARPE-19 cells displayed impaired apoptosis induction associated with significant downregulation of CHOP expression. Our evidence of this protective effect corroborates previous findings which demonstrate that adenoviral-mediated PERK knockdown protects ARPE-19 cells from ER stress-associated apoptosis following hydroquinone and visible light exposure (400–800 nm)-induced ER stress via CHOP downregulation 10 , 11 . Indeed, CHOP has been shown to sensitise cells to apoptosis by downregulating gene expression of the anti-apoptotic protein Bcl-2 and upregulating pro-apoptotic Bax 22 , 33 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Following PERK downregulation, ARPE-19 cells displayed impaired apoptosis induction associated with significant downregulation of CHOP expression. Our evidence of this protective effect corroborates previous findings which demonstrate that adenoviral-mediated PERK knockdown protects ARPE-19 cells from ER stress-associated apoptosis following hydroquinone and visible light exposure (400–800 nm)-induced ER stress via CHOP downregulation 10 , 11 . Indeed, CHOP has been shown to sensitise cells to apoptosis by downregulating gene expression of the anti-apoptotic protein Bcl-2 and upregulating pro-apoptotic Bax 22 , 33 .…”
Section: Discussionsupporting
confidence: 91%
“…PERK and its downstream signalling effectors have been shown to be essential in regulating the induction of autophagy in response to ER stress 41 . In ARPE-19 cells, autophagy can be induced by photooxidative or high-glucose environments that result in ER stress 11 , 42 . The impairment of autophagy has been extensively implicated in the ageing RPE and in the pathogenesis of AMD 24 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light-induced retinal degeneration models share many common pathogenic characteristics with AMD [ 32 ]. Models of light exposure have been used to study the regulation of retinal sphingolipids and ER stress in AMD [ 33 , 34 ]. HuPMCs with TKT knockdown were exposed to light stress to study further the roles of TKT in the Müller cells’ response to stress ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, autophagy might be a double-edged, increasing studies revealed that prolonged autophagy may lead to cell injury (Song et al, 2020). Therefore, it is crucial to clarifying the role of autophagy in IDD.…”
Section: Introductionmentioning
confidence: 99%